2002
DOI: 10.4141/s01-047
|View full text |Cite
|
Sign up to set email alerts
|

Eight years of crop rotation and tillage effects on crop production and N fertilizer use

Abstract: Soon, Y. K. and Clayton, G. W. 2002. Eight years of crop rotation and tillage effects on crop production and N fertilizer use. Can. J. Soil Sci. 82: 165-172. Although tillage systems and crop rotations can affect crop production and uptake of nutrients, their long-term effects, particularly their interactions, are not well-documented. Therefore, we measured the N, P, and K contents and yields of crops through two rotation cycles, especially wheat (Triticum aestivum L.), of four crop rotations managed under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Each phase of the rotation was present every year. Agronomic details of the trial have been described by Soon and Clayton (2002). Conventional tillage consisted of fall cultivation to 10-15 cm depth with a heavy-duty cultivator or disc, and two spring tillage operations with a field cultivator, followed by harrowing and packing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each phase of the rotation was present every year. Agronomic details of the trial have been described by Soon and Clayton (2002). Conventional tillage consisted of fall cultivation to 10-15 cm depth with a heavy-duty cultivator or disc, and two spring tillage operations with a field cultivator, followed by harrowing and packing.…”
Section: Methodsmentioning
confidence: 99%
“…In 1999, N applied was in the order: green manure > pea = canola > wheat (Table 3). Over an 8-yr period of the same trial, Soon and Clayton (2002) reported the following order of average straw N: canola > pea > wheat. All residues supplied more N in 1999 than 1998, presumably due to higher DM yields (Table 2) resulting from better rainfall distribution in 1999 than in 1998, when May and June were dry and July was excessively wet (Lupwayi et al 2004a).…”
Section: Initial Crop Residue Quality and N Addedmentioning
confidence: 97%
“…Each phase of the rotation was present each year. Agronomic details of the trial have been described by Soon and Clayton (2002). Conventional tillage consisted of fall cultivation to 10-15 cm depth with a heavy-duty cultivator or disc, and two spring tillage operations with a field cultivator, followed by harrowing and packing.…”
Section: Methodsmentioning
confidence: 99%
“…The main plots were tillage treatments (conventional tillage and zero tillage) and the subplots consisted of different crop sequences in rotation (Lupwayi et al 2004). The agronomic details of the trial have been described by Soon and Clayton (2002). Conventional tillage consisted of fall cultivation to 10-to 15-cm depth with a heavy-duty cultivator or disc, and two spring tillage operations with a field cultivator.…”
Section: Field Experimentsmentioning
confidence: 99%